Repair of a Rat Mandibular Bone Defect by Hypertrophic Cartilage Grafts Engineered From Human Fractionated Adipose Tissue - Cheng, Chen; Chaaban, Mansoor; Born, Gordian; Martin, Ivan; Li, Qingfeng; Schaefer, Dirk J.; Jaquiery, Claude; Scherberich, Arnaud (Frontiers in Bioengineering and Biotechnology, 2022)
Background：Devitalized bone matrix (DBM) is currently the gold standard alternative to autologous bone grafting in maxillofacial surgery. However, it fully relies on its osteoconductive properties and therefore requires defects with healthy bone surrounding. Fractionated human adipose tissue, when differentiated into hypertrophic cartilage in vitro, was proven reproducibly osteogenic in vivo, by recapitulating endochondral ossification (ECO). Both types of bone substitutes were thus compared in an orthotopic, preclinical mandibular defect model in rat. Methods：Human adipose tissue samples were collected and cultured in vitro to generate disks of hypertrophic cartilage. After hypertrophic induction, eight samples from two donors were implanted into a mandible defect in rats, in parallel to Bio-Oss® DBM granules. After 12 weeks, the mandible samples were harvested and evaluated by Micro-CT and histology. Results：Micro-CT demonstrated reproducible ECO and complete restoration of the mandibular geometry with adipose-based disks, with continuous bone inside and around the defect, part of which was of human (donor) origin. In the Bio-Oss® group, instead, osteoconduction from the border of the defect was observed but no direct connection of the granules with the surrounding bone was evidenced. Adipose-based grafts generated significantly higher mineralized tissue volume (0.57 ± 0.10 v.s. 0.38 ± 0.07, n = 4, P = 0.03) and newly formed bone (18.9 ± 3.4 % of surface area with bone tissue v.s. 3 ± 0.7 %, P < 0.01) than Bio-Oss®. Conclusion: Our results provide a proof-of-concept that adipose-based hypertrophic cartilage grafts outperform clinical standard biomaterials in maxillofacial surgery.